Characterization of Probiotics Isolated from Intestine of Mackerel Fish (Rastrelliger sp.) from Lembata Regency of East Nusa Tenggara - Daten, Helena; Ardyati, Tri; Jatmiko, Yoga Dwi (The Journal of Experimental Life Science, 2020)
The research aimed to isolate, characterize, and analyze the ability of lactic acid bacteria (LAB) potential as probiotics to produce hydrolase enzyme. The LAB was isolated using MRS agar by the spread plate method. The LAB characterization includes antimicrobial activity, tolerance to low pH, bile salt, salinity, autoaggregation properties, and ability to produce hydrolytic enzymes. The isolate which has the highest ability to inhibit Aeromonas hydrophila is KBP 3.3, while the isolate which inhibits the highest Streptococcus agalactiae is KBP 1.1.1. The KBP 3.3 and KBP 1.1.1 were able to survive at pH 1 for 24 hours with a survival rate of 93.6% and 98.3%. The KBP 3.3 and KBP 1.1.1 are tolerant to 7.5% bile salt concentrations for 24 hours of 99.46% and 99.11%. The KBP 3.3 is tolerant to 0.5 % salinity for 24 hours with the highest survival rate of 113.38%, while KBP 1.1.1 is 94%. The KBP 3.3 and 1.1.1 have autoaggregation properties of 92.18% and 87.84%. The KBP 3.3 produced the highest lipase enzyme, while KBP 1.1.1 produced the protease enzyme.Keywords: hydrolytic enzyme, lactic acid bacteria, mackerel, probiotic